Mapping the evolution of clusters: A meta-analysis - Mario A. Maggioni; Francesca Gambarotto; Teodora Erika Uberti (Fondazione Eni Enrico Mattei (FEEM), 2009)
This paper presents a meta-analysis of the cluster literature contained in scientific journals from 1969 to 2007. Thanks to an original database we study the evolution of a stream of literature which focuses on a research object which is both a theoretical puzzle and an empirical widespread evidence. We identify different growth stages, from take-off to development and maturity. We test the existence of a life-cycle within the authorships and we discover the existence of a substitutability relation between different collaborative behaviours. We study the relationships between a spatial and an industrial approach within the textual corpus of cluster literature and we show the existence of a predatory interaction. We detect the relevance of clustering behaviours in the location of authors working on clusters and in measuring the influence of geographical distance in co-authorship. We measure the extent of a convergence process of the vocabulary of scientists working on clusters.
Keywords: O18; R12; Z13; B41; 330; Cluster; Life-Cycle; Cluster Literature; Textual Analysis; Agglomeration; Co-Authorship